Analisis Spasial Zona Risiko Gempabumi Berdasarkan Intensitas Seismik dan Peak Ground Acceleration (PGA) di Provinsi Bengkulu Periode 2012–2021 - Farika, Nurahmi; Kusmita, Tri; Kurniawan, Widodo Budi (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Bengkulu Province is characterized by high seismic activity due to the influence of complex regional tectonic systems, which necessitates a comprehensive assessment of earthquake risk to support effective disaster mitigation. This study aims to delineate earthquake risk zones in Bengkulu Province based on Peak Ground Acceleration (PGA) and earthquake intensity. The analysis utilizes earthquake data recorded between 2012 and 2021 with magnitudes ≥ 3 and focal depths ranging from 0 to 100 km. Earthquake magnitudes originally reported as Mb, Mw, and Ms were converted to a uniform magnitude scale, namely surface wave magnitude (Ms). PGA values were calculated using the Gutenberg–Richter and McGuire empirical models, while earthquake intensity was estimated using an empirical relationship between surface wave magnitude and intensity. The results indicate that PGA values in Bengkulu Province range from 10 to 510 gal, with corresponding earthquake intensities varying from III to IX–X on the Modified Mercalli Intensity (MMI) scale. The highest earthquake risk is identified in Seluma Regency, whereas other regions exhibit low to moderate risk levels. The integrated spatial analysis of PGA and earthquake intensity provides a representative earthquake risk zonation that can serve as a scientific basis for earthquake mitigation planning and the implementation of seismic-resistant building design in Bengkulu Province.